1996
DOI: 10.1038/nm0496-463
|View full text |Cite
|
Sign up to set email alerts
|

Protection of auditory neurons from aminoglycoside toxicity by neurotrophin-3

Abstract: Hearing is conveyed from the auditory receptors, the hair cells in the organ of Corti, to the brain via the spiral ganglion neurons. Damage or loss of either spiral ganglion neurons or hair cells causes hearing impairment. Such hearing disorders are often permanent and can be caused by therapeutic agents, such as aminoglycoside antibiotics and cisplatin, or by aging, loud sounds, infections and mechanical injury (1). Brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3), members of the neurotrohin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(158 citation statements)
references
References 37 publications
8
145
2
3
Order By: Relevance
“…Within the developing cochlea, neurotrophins are differentially distributed, with NT-3 expressed predominantly in the supporting cells of the organ of Corti, and BDNF expressed only in hair cells (Farinas, et al, 2001). Further, many in vivo studies have reported that exogenous administration of neurotrophins (Ernfors et al, 1996;Kanzake et al, 2002;McGuinnes and Shepherd, 2005;Miller et al, 1997;Schindler et al 1995;Shepherd et al, 2005;Staecker et al, 1996Staecker et al, , 1998Zheng et al, 1995;Zheng and Gao, 1996) and other neurotrophic factors such as glial cell line-derived neurotrophic factor (GDNF) (Ylikoski et al, 1998;Yagi et al, 2000) can protect SG neurons in adult animals from injury and promote improved survival after various insults, including ototoxic drugs.…”
Section: The Role Of Neurotrophins In Survival Of Sg Neurons After Nementioning
confidence: 99%
“…Within the developing cochlea, neurotrophins are differentially distributed, with NT-3 expressed predominantly in the supporting cells of the organ of Corti, and BDNF expressed only in hair cells (Farinas, et al, 2001). Further, many in vivo studies have reported that exogenous administration of neurotrophins (Ernfors et al, 1996;Kanzake et al, 2002;McGuinnes and Shepherd, 2005;Miller et al, 1997;Schindler et al 1995;Shepherd et al, 2005;Staecker et al, 1996Staecker et al, , 1998Zheng et al, 1995;Zheng and Gao, 1996) and other neurotrophic factors such as glial cell line-derived neurotrophic factor (GDNF) (Ylikoski et al, 1998;Yagi et al, 2000) can protect SG neurons in adult animals from injury and promote improved survival after various insults, including ototoxic drugs.…”
Section: The Role Of Neurotrophins In Survival Of Sg Neurons After Nementioning
confidence: 99%
“…This degeneration has been associated with discontinued neurotrophic support from the organ of Corti (Ernfors et al 1995;Fritzsch et al 1999;Zilberstein et al 2012). Administration of exogenous neurotrophic factors has prevented SGC degeneration in multiple animal models of SNHL (for a review, see Ramekers et al 2012); SGCs are larger and more numerous after neurotrophic treatment than in untreated controls (Ernfors et al 1996;Richardson et al 2005;Shepherd et al 2005;Glueckert et al 2008;Agterberg et al 2008Agterberg et al , 2009Leake et al 2011;van Loon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these neurotrophins are also thought to contribute to neuronal maintenance in the adult inner ear (5). In the absence of hair cells, the neuroprotective effects of chronically delivered exogenous BDNF or NT-3 on SGNs in vivo has been demonstrated (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%